The interaction mechanism and the functionality of yeast protein with hydrophilic and hydrophobic bioactive molecules. (April 2023) - Sun, Haili; Sun, Yifei; Tang, Xin; Cui, Yuanmeng; Meng, Demei; Zhang, Yuyu; Li, Ku; Guo, Hui; Chen, Hai; Yang, Rui
Abstract: Yeast protein is a kind of yeast-source high-quality complete protein. The coexistence of bioactive molecules with yeast protein may influence its physicochemical property. This study discussed the interaction mechanism of yeast protein with two bioactive molecules, the hydrophobic curcumin and the hydrophilic epigallocatechin gallate (EGCG). Results indicated that curcumin and EGCG could interact with yeast protein with different binding stoichiometric numbers (0.8109 ± 0.0695 and 2.7248 ± 0.2422) and binding constants ((3.8152 ± 0.0078) × 10 4 and (1.1875 ± 0.0440) × 10 5 ), respectively. Both EGCG and curcumin decreased the α-helix content while increased the β-sheet proportion, and co-binding remarkably reduced the α-helix proportion relative to the single ligand binding. The co-binding of these two compounds decreased the association extent of the yeast protein, which in turn reduced the diameter of yeast protein-EGCG-curcumin complex. The binding of EGCG with yeast protein improved the thermal stability of curcumin. Moreover, the co-binding improved the emulsification stability of yeast protein, and curcumin exhibited a more remarkable effect in improving the foamability. This work provides a theoretical basis for clarifying the interaction mechanisms of hydrophobic/hydrophilic molecules with yeast protein, and extends the potential applications of the novel fungus protein sources for food function enhancement and bioactive molecule stabilization. Graphical abstract: Image 1 Highlights: Curcumin and EGCG bind to yeast protein (YP) with different binding stoichiometry. EGCG and curcumin cause the structural change of YP by increasing the β-sheet content. Co-binding of EGCG with YP effectively improve the thermal stability of the curcumin. Curcumin and EGCG improve the foamability and emulsibility of YP to different extent.